Discovery and in vivo effects of novel human natriuretic peptide receptor A (NPR-A) agonists with improved activity for rat NPR-A. Issue 24 (15th December 2017) - Iwaki, Takehiko; Tanaka, Taisaku; Miyazaki, Kazuo; Suzuki, Yamato; Okamura, Yoshihiko; Yamaki, Akira; Iwanami, Makoto; Morozumi, Naomi; Furuya, Mayumi; Oyama, Yoshiaki
Graphical abstract: Abstract: Natriuretic peptide receptor A (NPR-A) agonists were evaluated in vivo by optimizing the structure of quinazoline derivatives to improve agonistic activity for rat NPR-A. A 1, 4- Cis -aminocyclohexylurea moiety at 4-position and hydroxy group ofd -alaninol at 2-position on the quinazoline ring were found to be important factors in improving rat NPR-A activity. We identified potent quinazoline and pyrido[2, 3- d ]pyrimidine derivatives against rat NPR-A, with double-digit nanomolar EC50 values. The in vivo results showed that compound56b administered at 1.0 mg/kg/min significantly increased plasma cGMP concentration and urine volume in rats. We discovered novel potent NPR-A agonists that showed agonistic effects similar to those of atrial natriuretic peptide.